Clinical and echocardiographic phenotype of cardiac wasting in patients with advanced cancer - Anker, Markus; Khan, Muhammad Shahzeb; Nikolski, Anja; Porthun, Jan; Arshad, Muhammad Sameer; Hadzibegovic, Sara; Lena, Alessia; Kretzler, Lucie; Hella, Jonathan L.; Witkowski, Marco; Rieger, Kathrin; Ahn, Johann; et al. (European journal of heart failure, 2025)
Aims Cardiac wasting-associated cardiomyopathy in patients with advanced cancer is characterized by loss of left ventricular (LV) mass and independently associated with poor prognosis. Better understanding of this very prevalent cardiomyopathy is urgently needed. Methods and results Overall, 398 patients with active, mostly advanced cancer without significant cardiovascular disease (mean LV ejection fraction [LVEF] 64.3 ± 0.2%) or active infection were prospectively examined (mean age 60 ± 1 years, 50% women, body mass index 25.0 ± 0.2 kg/m2, 26% cachectic). Patients were categorized and compared by quartiles of LV mass/height2. LVEF, global longitudinal strain (GLS), and anticancer therapy naive status were similar across quartiles. Patients in Q1 (lowest LV mass quartile) were younger, more likely cachectic, had lower: BMI, 10-step stair-climbing power, tricuspid annular plane systolic excursion (TAPSE), stroke volume, cardiac output, and higher heart rate. In repeat follow-up assessments after 140 ± 8 days (n = 143), LVEF, TAPSE, LV mass, left atrial volume, and GLS were found reduced (all p ≤ 0.002). Only in those with above-median LV mass at baseline, cardiac output and heart rate increased during follow-up - in those with below-median LV mass, mitral E/A decreased. Conclusions Patients with advanced cancer with low LV mass have a distinct phenotype characterized by lower cardiac chamber volumes, stroke volume, and cardiac output, but normal LVEF and GLS that may be the distinct feature of cardiac wasting-associated cardiomyopathy.